Entropy analysis in a second‐grade nanoliquid influenced by an exponential space‐dependent heat source and Arrhenius activation energy. Issue 6 (27th April 2022) - Subbarao, K.; Elangovan, K.; Gangadhar, Kotha
Abstract: Addressing the second‐grade nanofluid flow over a porous stretching sheet based on entropy generation is done in this study. In the mathematical modeling, the revised Buongiorno model is utilized. Employing exponential space‐dependent heat generation and Heat transfer subject to melting effect is implemented. Energy and concentration expressions are retained based on the impact of activation energy, Joule heating, nonlinear thermal radiation, and viscous dissipation. Implementation of solutions for a standard transformation, governing equations, and the numerical procedure is done. Several governing parameters are discussed based on the effect of comprehensive effects of the flow region. A thicker thermal boundary layer is obtained by increasing the magnetic strength and Brownian movement. Thermophoresis increases similarly while the trend takes place, and for the melting parameter, the reverse order is noted. Melting parameter increases with increase in entropy generation rate and Brinkman number increases with reduction in Bejan number. In the literature, it is found that the situation is limited for the obtained results in the model. Higher entropy generation rates are exhibited for the demonstration of magnetic force. From the results, it is observed that the design parameters will consequently optimize the heat transfer in the assessment of industrial processes.